Organization of the health-forming system in general education schools - A.S. Kasmalieva, (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop and substantiate the theoretical and applied aspects of creating a health-forming educational system based on the implementation of the pedagogical and health-improving potential of an educational institution. Methods and structure of the study. The methods of generalization, systematization, methods of analysis of normative documents, the study and generalization of the advanced pedagogical experience of general education schools were used to specify the main goals and objectives of the health-forming pedagogical system and develop the content of its main elements for the full implementation of the pedagogical and health-improving potential of an educational institution for the formation of health, timely socialization and prevention of deviant behavior of students. Results and conclusions. A model of a health-forming system has been developed, which is based on the use of health-saving educational and health technologies and is aimed at mastering a complex of knowledge about health, building an individual strategy for the formation and preservation of the health of schoolchildren. It was revealed that the main elements of the health-forming pedagogical system are organizational and pedagogical technologies; educational technologies; health-improving technologies; psychological and pedagogical technologies; socially adaptive and personality-developing technologies.